Diagnostic accuracy of transvaginal ultrasound (TVUS) and diffused weighted imaging (DWI) in female patient with ovarian cancer: a systematic review and meta-analysis / Ainul Shafiqah Zulkifli, Mohd Zulfadli Adenan - Zulkifli, Ainul Shafiqah; Adenan, Mohd Zulfadli (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
This review is aimed to compare the diagnostic accuracy of transvaginal ultrasound (TVUS) and diffused weighted image (DWI) in assessing ovarian cancer. An extensive search was performed in Dimension, Google Scholar and Wiley Online Library for studies published from January 2011 to April 2020. Following the screening, the eligibility of the studies was checked. Then, the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) checklist was adapted to assess the quality of each of the study being reviewed. The information on the diagnostic performance of TVUS and DWI were extracted from each of the studies. The heterogeneity of the studies was explored. Overall, pooled sensitivity, specificity, LR+, and LR− of TVUS for detecting ovarian cancer were 75% (95% confidence interval [CI]=57%-87%), 92% (95% CI=80%-97%), 8.97 (95% CI=3.21-25.08), and 0.28 (95% CI=0.14-0.52), respectively. High heterogeneity was established for sensitivity (I²=92.28%; Cochran Q=38.85; p=0.00). Furthermore, high heterogeneity was found for specificity (I²=88.54%; Cochran Q=26.17; p=0.00). TVUS has high specificity for detection of ovarian cancer. TVUS should be considered as good enough for being used in clinical settings with limited resources.